Neither sexist nor feminist: Machos Alfa’s ambiguity and equidistance regarding gender equality - Chicharro-Merayo, Mar; Gil Torres, Alicia (Historia y Comunicación Social, 2026)
This work researches the communication ecosystem created around the series Machos Alfa (Netflix, 2022), focused on relationships between genders, the advances of feminism and new masculinities. It analyzes its promotion campaign (how the product is framed), its message (its text) and its reception (readings made by viewers), using a qualitative methodology, linked to Cultural Studies. The relevance, ideological controversy and polarization around this issue are revealed, as well as its usefulness for the market. These peculiarities invite reflection on the potential of television fiction to promote a more rigorous and critical approach to gender in the treatment of equality and feminist debate.